Postpartum Depression: Husbandly Support and Self-Acceptance Factor - Nurul Hartini, Kartika Rukmi Palupi, (Opción, 2019)
This research aimed to investigate the postpartum depression. The new life stage and the new role a mother require women to adapt via research survey, involving 72 respondents who tend to experience postpartum depression. The data were collected using the EPDS questionnaire (Edinburgh Postnatal Depression Scale), which contains ten items with a value of α = 0.814. The results showed that husbandly support and self-acceptance simultaneously related to depression in postpartum mothers. In conclusion, preventive measures on depressive tendencies are critical for parents before planning to have children in order to reduce the likelihood of postpartum depression.